2019
DOI: 10.1371/journal.pone.0218756
|View full text |Cite
|
Sign up to set email alerts
|

Association between culture of patient safety and burnout in pediatric hospitals

Abstract: Conclusion The study evidenced the influence of all patient safety domains for the development of burnout syndrome in pediatric professionals. Also, it was identified that the organizational climate is the main determinant of burnout, especially in what refers to "teamwork between units".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
1
19
0
1
Order By: Relevance
“…These results were consistent with the literature. For instance, one study found that burnout grades among health care workers were associated with patient safety (de Lima Garcia et al, 2019 ). In addition, another study examined paediatric nurses' QOL and found that lower QOL was associated with poorer quality of patient care (Berger et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with the literature. For instance, one study found that burnout grades among health care workers were associated with patient safety (de Lima Garcia et al, 2019 ). In addition, another study examined paediatric nurses' QOL and found that lower QOL was associated with poorer quality of patient care (Berger et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, burnout was negatively correlated with nurses' QOL (Erkorkmaz et al, 2018 ). Finally, the low QOL and high burnout levels among paediatric nurses may negatively impact patient safety (de Lima Garcia et al, 2019 ; Hall et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] It has been suggested that burnout may be associated with issues relating to patient safety, as both burnout and patient safety relate to organisational, social and individual factors which depend on environmental resources. [13] There is also evidence that medical errors and their sequalae can in turn cause or worsen practitioner burnout and mental health problems, an effect that may be compounded by organisational factors including an organisational culture of blame, inadequate personal support and suboptimal administrative support [14,15]. Two key systematic reviews examined the relationship between burnout and patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…How organisations deal with these events and support the patients and staff involved is important. Having a well-developed safety culture of shared values, attitudes and patterns of behaviour regarding safety [ 7 ] can reduce adverse events [ 8 , 9 ] and staff burnout [ 10 ]. Second victim recovery is also supported by active incident learning [ 7 ] and debriefing processes [ 6 ].…”
Section: Introductionmentioning
confidence: 99%